Case Report: Gas in the esophagus, stomach wall and portal vein with congenital hypertrophic pyloric stenosis - Yao, Na; Zhang, Wenxin; Gao, Qi; Lu, Chaoxiang; Wang, Qi (Frontiers in Pediatrics, 2024)
Background: CHPS dramatically affects infant growth and development and can even cause aspiration resulting from esophageal reflux. There is potential danger. CHPS is common, while CHPS with gas in the stomach wall and portal vein is rare. Gas in the stomach wall and portal vein are often the key features of more serious disease. It can be easily mistaken as a serious disease when patients with CHPS have gas in the stomach wall and portal vein.Case presentation: A 56-day-old baby was hospitalized for aspiration pneumonia after vomiting without bile for 20 days. Compared with vomiting, which is the most common symptom, pneumonia tends to attract more attention. Because of pneumonia, a chest CT scan was performed and revealed massive gas accumulation in the walls of the esophagus, stomach, and portal vein. Therefore, NEC was considered first and was treated conservatively for one week. However, the vomiting continued, and CHPS was confirmed by ultrasound. The delay in CHPS diagnosis was due to insufficient recognition of the signs of gas accumulation. Because of inexperience and lack of knowledge about CHPS with gastrointestinal pneumatosis, physicians failed to make an early accurate diagnosis.Case 2 was a 29-day-old male who was admitted to the hospital with vomiting without bile. He was examined by ultrasound, which revealed gas in the stomach wall and portal vein after admission to the hospital. No peritonitis was found after a detailed and comprehensive physical examination. Emergency life-threatening diseases such as NEC were quickly ruled out. He received surgery as soon as possible and had an uneventful recovery with no complications.Conclusion: CHPS may present with gas in the gastric or esophageal wall and portal vein, which is not a contraindication to surgery.